One-Year Risk Prediction of Elevated Serum Uric Acid Levels in Older Adults: A Longitudinal Cohort Study - Zhang D; Xu X; Ye Z; Zhang Z; Xiao J (Clinical Interventions in Aging)
Dexian Zhang,1,2,* Xinxin Xu,2,3,* Zhibin Ye,1,2 Zhenxing Zhang,1,2 Jing Xiao1,2 1Department of Nephrology, Huadong Hospital, Fudan University, Shanghai, People’s Republic of China; 2Shanghai Key Laboratory of Clinical Geriatric Medicine, Huadong Hospital, Fudan University, Shanghai, People’s Republic of China; 3Clinical Research Center for Geriatric Medicine, Huadong Hospital, Fudan University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhenxing Zhang; Jing Xiao, Department of Nephrology, Huadong Hospital, Fudan University, Shanghai, People’s Republic of China, Email contraindication@163.com; jingxiao13@fudan.edu.cnObjective: To develop and externally validate a nomogram to predict elevated serum uric acid (SUA) levels in older adults.Study Design: This is a longitudinal Chinese cohort study.Methods: A cohort of 2788 older adults was established at Huadong Hospital, followed-up for at least one year, and screened for risk factors for elevated SUA levels. A logistic regression model was built to predict elevated SUA, and its performance was validated.Results: The risk prediction model showed good discrimination ability in both the development cohort (area under the curve (AUC) =  0.82; 95% confidence interval (CI) =0.79~0.86) and the external validation cohort (AUC=0.76; 95% CI=0.70~0.82). The model was adequately calibrated, and the predictions correlated with the observed outcome (χ2 =  6.36, P =  0.607). Men were more prone to elevated SUA levels than women were, and a baseline SUA level ≥ 360 μmol/L was a common risk factor for both males and females. Proteinuria status was an additional risk factor for males, whereas a baseline estimated glomerular filtration rate (eGFR)< 60 mL/min· 1.73 m2 and diabetes status were additional risk factors for females.Conclusion: The externally validated nomogram, which is predictive of elevated SUA in older adults, might aid in the detection of individual diseases, the development of preventive interventions and clinical decision-making.Keywords: elevated serum uric acid, prediction nomogram, risk factor